The Role of the Francisella Tularensis Pathogenicity Island in Type VI Secretion, Intracellular Survival, and Modulation of Host Cell Signaling - Bröms, Jeanette; Sjöstedt, Anders; Lavander, Moa (Frontiers in Microbiology, 2010)
Francisella tularensis is a highly virulent gram-negative intracellular bacterium that causes the zoonotic disease tularaemia. Essential for its virulence is the ability to multiply within host cells, in particular monocytic cells. The bacterium has developed intricate means to subvert host immune mechanisms and thereby facilitate its intracellular survival by preventing phagolysosomal fusion followed by escape into the cytosol, where it multiplies. Moreover, it targets and manipulates numerous host cell signalling pathways, thereby ameliorating the otherwise bactericidal capacity. Many of the underlying molecular mechanisms still remain unknown but key elements, directly or indirectly responsible for many of the aforementioned mechanisms, rely on the expression of proteins encoded by the Francisella pathogenicity island (FPI), suggested to constitute a type VI secretion system (T6SS). We here describe the current knowledge regarding the components of the FPI and the roles that have been ascribed to them.